Effect of crop rotational position and nitrogen supply on root development and yield formation of winter wheat - Arnhold, Jessica; Grunwald, Dennis; Braun-Kiewnick, Andrea; Koch, Heinz-Josef (Frontiers in Plant Science, 2023)
The lower yield of wheat grown after wheat (second wheat) compared with first wheat after a break crop is frequently attributed to fungal disease occurrence, but has also been found without visible disease infection, thus, other factors might be responsible for the lower yield of the second wheat. The aims of this study were to analyze the effects of growing wheat as monoculture, as well as first and second wheat after oilseed rape in a long-term field experiment over three years on (i) aboveground biomass formation, root development and nutrient acquisition during the growing season, (ii) take-all occurrence, and (iii) grain yield and yield components. Root length density of winter wheat was significantly higher after oilseed rape as pre-crop than after wheat, which was independent of take-all occurrence in the subsoil. Differences in wheat aboveground biomass occurred at early growth stages and were persistent until harvest. Grain yield loss correlated well with take-all disease severity in a wet year but yield differences occurred also in a dry year without visible fungal infection. Thus, an effect of the crop rotational position of wheat beyond take-all disease pressure can be assumed. Overall, wheat root length density might be the key to understand wheat biomass formation and grain yield in different crop rotational positions.